Edmund W. Gordon producing knowledge, pursuing understanding - Yeakey, Carol Camp. (Bingley, UK : Emerald, 2002)
The initial volume in this new series focuses on the work of Edmund W. Gordon, the John M. Musser Professor of Psychology Emeritus at Yale University. Gordon had a tremendous influence on contemporary thinking in psychology, education and social policy and the implications of his work for the schooling of lower status youth and children of color, in America. For some, this volume will reacquaint them with Gordon and many of the young persons, now senior scholars themselves, who have learned from him. For others, this volume will simply inform them of the magnitude of the man and the legacy of researchers and research he has spawned. This important work challenges some of the basic assumptions under-pinning American social science research. Scholars from diverse fields of economics, anthropology, law, education, political science, sociology, psychology, and public health question traditional assumptions with respect to low status populations and persons of color, and analyze some of the intended and unintended consequences of those assumptions. The essays in this volume are well reasoned, provocative in the subject matter that they cover, and thoughtful in their conclusions. There is little doubt that the central focus of the book - the influence of Edmund W. Gordon and his liberatory scholarship - is a topic the examination of which is long overdue. The volume is divided into four sections: relevance of social divisions in research and development; population sensitive intervention; explanatory investigations; and, context responsibility. The final word in the volume, in the Epilogue, rightfully belongs to Edmund W. Gordon himself.
Preface / Carol Camp Yeakey -- Introduction / Carol Camp Yeakey -- Social context of emotion in black adolescents: impact of principles on process and products / David Rollock -- Beyond deficits and difference psychological integrity in developmental research / A. Wade Boykin, Brenda A. Allen -- Exploring African-American adolescents' home and school psychosocial contexts of career development / Margaret Beale Spencer, Christopher Ashford, Tara Thompson, Tracey Hartman -- Race, class, and educational opportunity: trends in the sociology of education / Edgar G. Epps, Carolyn D. Epps -- School readiness: implications for day care and early childhood education for low-income children / Norris M. Haynes, Michael Ben-Avie, Walter Gilliam -- Building capacity for health empowerment in African-American communities / Ronald Braithwaite, Malika Braithwaite, Micah Milton -- Community building to achieve educational equity / Angela Glover Blackwell, Heather Bent Tamir -- Contemporary assessment in the context of culture and pedagogy: the assessor as responsible scholar / Sylvia T. Johnson -- Postsecondary access and degree attainment of African Americans 1976-1996: a dream fulfilled or a dream still deferred? / Antoine M. Garibaldi -- Controlled choice: A new and effective desegregation method / Charles V. Willie -- The personal in education / Erwin Flaxman, Jeanne Weiler -- Intelligence as a dimension of diversity implications for pedagogical assessment / Eleanor Armour-Thomas -- Implications of an ecological model for directed behavior change / Ana Mari Cauce -- Contextualism, phenomenology, and methodological problems in the social sciences / Fayneese S. Miller, Robert L. Biral -- Conceptualizing the African / Edmund T. Gordon, Mark Anderson -- Post-industrial economic experiences of African-American men, 1973-1993 / Jessica Gordon Nembhard -- The work of Edmund W. Gordon: accountability, responsibility, and standards / Linda Darling-Hammond -- Prophetic social scientists / John H. Stanfield -- Research, scholarship, and social responsibility: social imperatives for a democratic society / Carol Camp Yeakey -- Production of knowledge and pursuit of understanding / Edmund W. Gordon.
Description based on print version record.
Keywords: Gordon, Edmund W; Multicultural education -- Study and teaching; Philosophy & theory of education; Multicultural education; Education -- Research